2017
DOI: 10.26603/ijspt20171121
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder External Rotator Eccentric Training Versus General Shoulder Exercise for Subacromial Pain Syndrome: A Randomized Controlled Trial

Abstract: Background: Shoulder pain affects up to 67% of the population at some point in their lifetime with subacromial pain syndrome (SAPS) representing a common etiology. Despite a plethora of studies there remains conflicting evidence for appropriate management of SAPS.Purpose: To compare outcomes, for individuals diagnosed with SAPS, performing a 6-week protocol of eccentric training of the shoulder external rotators (ETER) compared to a general exercise (GE) protocol. Study Design: Randomized controlled trialMetho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 52 publications
(60 reference statements)
4
59
0
3
Order By: Relevance
“…Scrutiny of reference lists identified one potentially relevant study, but on closer inspection it did not fulfil the inclusion criteria. In total, we included seven studies reported in eight articles [25, 26, 32, 3741]. The search process and results are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scrutiny of reference lists identified one potentially relevant study, but on closer inspection it did not fulfil the inclusion criteria. In total, we included seven studies reported in eight articles [25, 26, 32, 3741]. The search process and results are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two were conducted in the United States and five in Europe. Of the seven studies, six [25, 26, 3740] compared eccentric exercise with other exercise. One [32] compared painful eccentric exercise (above the pain threshold: VAS < 40–50 mm) with pain-free eccentric exercise (VAS = 0 mm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on individuals with subacromial pain syndrome, 6-week general exercises were compared to eccentric exercises on the external rotators of the shoulder, and both treatments had a similar effect on UQYBT responses. [ 21 ] However, it was reported that the low number of subjects in the study might be a factor in the UQYBT results. Wilk et al reported that T10 exercises improved neuromuscular control and contributed to dynamic stabilization by activating the rotator cuff muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Різноманітні варіації вправ для таких хворих продемонстрували високу ефективність. Достатньо високі результати були отримані при виконанні вправ як під наглядом спеціаліста, так і вправ за домашньою програмою без постійного нагляду [15,16].…”
Section: вступunclassified